Use of a small domain of the T1 lipase as a protein scaffold - Leow, Adam Thean Chor; Salleh, Abu Bakar; Raja Abdul Rahman, Raja Noor Zaliha; Basri, Mahiran; Baharum, Hafidza (2012)
The present invention pertains to the use of a small domain of T1 lipase as a scaffold protein for the engineering of artificial proteins, specifically enzymes. The zinc binding domain of the T1 lipase comprises a helix-loop-helix three dimensional fold which is used according to the subject invention as a protein scaffold for the design of functional mini proteins like for example a mini lipase. The protein scaffold according to the invention is stabilized by the introduction of new disulfide bonds, while the solubility of the new protein scaffold is maintained by the optional introduction of charge residues. The invention furthermore provides the use of the small domain of T1 lipase as a scaffold protein, the new designed conformational active miniprotein, and processes for the manufacture of artificial proteins.